Increasing physical activity in the vehicle with an interactive seating system in a male sample. Issue 4 (3rd April 2023) - Lampe, Dario; Deml, Barbara
Abstract: An interactive seating system (IASS) was compared to a state-of-the-art massage seating system (MS) regarding the potential of reducing health risks from prolonged sitting in the vehicle. The study investigated if the systems (1) increase heart rate, which is associated with reduced metabolic and cardiovascular risks; (2) activate muscles with the potential to reduce musculoskeletal pain; (3) influence seating comfort and discomfort. The systems were compared in a passenger scenario in a laboratory study (30 male subjects). Only the use of the IASS significantly elevated the heart rate. Muscle activity showed tendencies to increase in the lower back only while using the MS. In comparison, the IASS activated all six captured muscles. Significantly less discomfort was found for the IASS compared to the MS. In comparison to the MS, the IASS showed a substantially higher potential for reducing health risks from static sitting in the vehicle. Practitioner summary: This laboratory study compared the effects of a novel automotive interactive seating system with those of a state-of-the-art massage seating system. Muscle activity, heart rate and discomfort indicated that the IASS has a significantly higher potential to reduce health risks associated with static seating in a vehicle. Abbreviations: AB: air bladder; AC: active condition; ADSS: active dynamic seating system; CLBP: chronic lumbar back pain; ECG: electrocardiography; EMG: electromyography; IASS: interactive seating system; MS: massage seating system; PC: passive condition; PDSS: passive dynamic seating system; RMS: rootmean-square; TI: time interval